Deformation Mechanisms of Blueschist Facies Continental Metasediments May Offer Insights Into Deep Episodic Tremor and Slow Slip Events. Issue 10 (21st October 2022) - Giuntoli, Francesco; Viola, Giulio; Sørensen, Bjørn Eske
Abstract: Exhumed fossil subduction zones are archives of the deformation conditions and mechanisms from depths not directly accessible. Microstructural analysis of samples exhumed therefrom offers insights into the micromechanics and deformation processes associated with subduction such as earthquakes, slow earthquakes, and aseismic creep. Subducted and exhumed continental metasediments of the Tuscan Metamorphic Units of the Italian Northern Apennines contain a mylonitic foliation and quartz and carpholite dilational hydroshear veins with crack‐and‐seal textures, both developed at blueschist facies conditions (350–400°C, ∼1 GPa). As shown by overprinting relationships and mineral assemblages, these two structure types formed broadly coeval within the stability field of carpholite. Metaconglomerates and metaquartzarenites deformed mainly by dissolution‐precipitation creep and secondary by dislocation creep. Microstructural and electron backscatter diffraction analyses of the veins suggest only limited recrystallization of quartz fibers by subgrain rotation recrystallization, with adjacent metapelite bands acting as decollement horizons, likely by slip on the basal plane of phyllosilicates. We estimated differential stresses of 43–55 MPa and strain rates between 10 −13 and 10 −14 s −1 from the vein recrystallized quartz fibers. We propose these microstructures and deformation mechanisms to represent a geological evidence of deep episodic tremor and slow slip events in subducted continental metasediments. Pore pressure cyclically reached supralithostatic values triggering tremors causing fracturing of all involved lithotypes. Likely, slow slip was accommodated preferentially by slip on phyllosilicate bands. Aseismic creep occurred mainly by dislocation creep with subgrain rotation recrystallization in vein quartz, slip on the basal plane of phyllosilicates, and dissolution and precipitation creep in the host rock. Plain Language Summary: Rocks exhumed from great depth can help us to investigate processes otherwise non directly accessible. The Italian Northern Apennines comprise exhumed continental sediments that were deformed and metamorphosed at depths of 30–40 km and temperatures of 350–400°C. Broadly coeval continuous and discontinuous deformation is documented as highly deformed zones (shear zones) and veins. We used microstructural analyses and electron microscopy techniques to reconstruct how these rocks deformed and the structures formed. Quartz‐rich metasediments deformed mainly by dissolution and precipitation processes. Weak phyllosilicate‐rich bands accommodated deformation likely by slip on their platy basal planes. Fluid pressure cyclically reached high values that caused failure of the metasediments, with subsequent migration of portion of the fluid and formation of the veins. Veins display only a limited amount of crystal plastic deformation. Quartz paleopiezometry and flow law suggest low differential stresses and average geological strain rates for the deformation of veins. We propose that these structures can be seen as a possible geological record of deep episodic tremor and slow slip events, low intensity and long lasting seismic events associated with slip transients faster than average plate motion. Key Points: Coeval dilational hydroshear veins and mylonites may shed light on deformation mechanisms of deep episodic tremor and slow slip events Dilational hydroshear veins formed by incremental crack‐seal at supralithostatic pore pressure values and deformed by dislocation creep Blueschist facies mylonites formed mainly by a combination of dissolution‐precipitation creep and slip along phyllosilicate bands